Massive Intraperitoneal Haemorrhage due toUterine Fibroid in Pregnancy: A Case Rerort and Literature Review - E Hummedia, Moawia (مجلة الجزيرة للعلوم الصحية; مجلد 11 عدد 1 (2015), 2015)
This is a report of a case of massive intraperitoneal haemorrhage during the third trimester of pregnancy due to rupture of coronary vessels overlying uterine Leiomyoma. Diagnosis was made after exploratory laparotomy. Emergency caesarean section and myomectomy were performed. The objective of this case report is to highlight diagnostic challenges, aggressive resuscitations, and prompt multi disciplinary interventions of unusually rare case during late pregnancy, and review of literature.